Effect of processing temperatures on mechanical properties of oil palm empty fruit bunch-filled PVC extrudates - Bakar, A. A. (SAGE Publications, 2009)
The influence of extrusion processing temperature profiles on the mechanical properties of oil palm empty fruit bunch-filled poly(vinyl chloride) extrudates was investigated. Only the poly(vinyl chloride) (PVC), acrylic and chlorinated polyethylene extrudates filled with 10 phr oil palm empty fruit bunch (OPEFB) were able to be extruded successfully as the extrusion processing temperature profiles increased. The extrudates containing 20 phr OPEFB were severely distorted even though the processing temperature was increased to the maximum level. The impact strength, flexural modulus and strength, and yield stress and strain at break of extrudates filled with 10 phr OPEFB were insignificantly affected by the increase of extrusion processing temperature and fusion level of PVC.